Sustainable manufacturing system applying on eco-design products. (2022) - Subharaj, C.; Jerin Leno, I.; Shivashankara,; Vivek, S.; Joe Patrick Gnanaraj, S.; Appadurai, M.
Abstract: In this research intends to investigate the usage of two environmentally friendly design improvement methodologies to get better results in the production and user phases. During the design phase, raw material selection, manufacturing procedures, and environmental repercussions such as global warming, greenhouse gas emissions, and energy usage were all addressed. Eco-design concepts are integrated throughout the product's life cycle by using current and planned designs. The study's other goal is to consider numerous outputs from the product development process as well as sustainability practices in relation to environmental improvement in the present and future. These designs contribute to environmental preservation by drastically lowering pollution. Products that are environmentally friendly might be manufactured from scratch recycled materials.